Understanding the psychology of trust between patients and their community pharmacists - Gregory, Paul A. M. (Can Pharm J (Ott), 2021)
BACKGROUND: Pharmacists need patients to trust them in order to support best possible health outcomes. There has been little empirical work to test the widely stated claim that pharmacists are the “most trusted” health care professional. This study was undertaken to characterize the factors that shape public trust of individual pharmacists and the profession as a whole. METHODS: An exploratory qualitative study was undertaken. Semistructured interviews with 13 patients from 5 different community pharmacies were completed. Interview data were transcribed, coded and categorized to identify trust-enhancing and trust-diminishing factors influencing patients’ perceptions of pharmacists. RESULTS: Four trust-diminishing factors were identified, including the business context within which community pharmacy is practised, lack of transparency regarding pharmacists’ remuneration, lack of awareness of how pharmacists qualify and are regulated and inconsistent previous experiences with pharmacists. Four trust-enhancing factors were identified, including accessibility, affability, acknowledgement and respect. DISCUSSION: This study illustrates that trust-diminishing factors appear to be somewhat outside the day-to-day control of individual community pharmacists, while trust-enhancing factors are elements that pharmacists may have greater personal control over. Further research is required to better understand these factors and to develop a more generalizable understanding of how patients develop trust in their pharmacists. Can Pharm J (Ott) 2021;154:xx-xx.